Motives of Social Media Usage and Effects to Housewives Well-Being in Cirebon City Indonesia - Nurfalah, Farida; Abdul Hamid, Norsiah; Sobhi Ishak, Mohd; Mohd Rashid, Sabrina; Nurudin, (International Journal of Psychosocial Rehabilitation, 2020)
Women dominate in general; they beat men on social media, such as Facebook, Instagram, and Twitter. Although the literature on motives for using social media is dominated by women, the findings do not fully reflect the motives among Indonesian housewives to use social media due to some costs. This study explores the motives of housewives about the use of social media and its effects on their well-being. This study adopted a mixed-methods approach. The survey was chosen through snowball sampling. The results of the study explained that 1). The identities of housewives who use social media in Indonesia are mostly from Cirebon, living in Cirebon district, with a bachelor's degree, with a home content income of Rp. 5,000,000., and above with tree households living in the same house. The use of social media in the form of Whatsapp and Instagram, with a usage time of about five hours. 2). Motivation of housewives uses social media as a communication medium in interacting socially with other social media users. 3). The impact of the use of social media among housewives: they can support each other and share whatever activities they do, look for health tips and tips on taking care of the household, which in the end they live and enjoy their daily activities, can interact well through social media, carrying out important activities, they can overcome their problems well, live a good life, believe in their future, and believe that they are respected by others. Their feelings are often positive and often good, often pleasant, often joyful, and never angry.